Facing the Holy Ark, in Words and in Images - Fraade, Steven D. (Near Eastern archaeology, 2019)
The ark of the covenant was central to the plan of the Jerusalem Temple and the wilderness tabernacle before it, as the vessel was located in the structures’ holiest, innermost domain. Despite its importance, the ark of the covenant was invisible to virtually all Israelites.1 Even while the ark was being assembled, disassembled, and transported in the wilderness, the Levitical Kohathites were instructed to shield it from view, including their own (Num 4:5-20). One of the chief obligations of Aaron and his descendants was to deny access to anyone else, including the Levites, to the Holy of Holies, which housed the ark alone, or risk death (Num 18:1-7, 22-23).